Protective effects of Moringa oleifera Lam. leaves against arsenic–induced toxicity in mice - Afzal Sheikh; Fouzia Yeasmin; Smita Agarwal; Mashiur Rahman; Khairul Islam; Ekhtear Hossain; Shakhawoat Hossain; Md Rezaul Karim; Farjana Nikkon; Zahangir Alam Saud; Khaled Hossain (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To evaluate the protective role of leaves of Moringa oleifera (M. oleifera) Lam. against arsenic-induced toxicity in mice. Methods: Swiss albino male mice were divided into four groups. The first group was used as non-treated control group while, the second, third, and fourth groups were treated with M. oleifera leaves (50 mg/kg body weight per day), sodium arsenite (10 mg/kg body weight per day) and sodium arsenite plus M. oleifera leaves, respectively. Serum indices related to cardiac, liver and renal functions were analyzed to evaluate the protective effect of Moringa leaves on arsenic-induced effects in mice. Results: It revealed that food supplementation of M. oleifera leaves abrogated the arsenic-induced elevation of triglyceride, glucose, urea and the activities of alkaline phospatase, aspartate aminotransferase and alanine aminotransferase in serum. M. oleifera leaves also prevented the arsenic-induced perturbation of serum butyryl cholinesterase activity, total cholesterol and high density lipoprotein cholesterol. Conclusions: The results indicate that the leaves of M. oleifera may be useful in reducing the effects of arsenic-induced toxicity.